The Minimalist Lifestyle as Qur’anic Practice: A Living Qur’an Study of Surah Al-A‘raf Verse 31 among UIN Sunan Kudus Students - Lestari, Dwi Ayu; Atabik, Ahmad; Muzakky, Althaf Husein (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
This study explores how students at UIN Sunan Kudus interpret and practice the message of Surah Al-A‘raf verse 31 through the adoption of a minimalist lifestyle. Using a qualitative phenomenological approach within the Living Qur’an framework, the research investigates how this verse functions not as a distant command, but as a daily reference for living with purpose, moderation, and awareness. Data were collected through in-depth interviews and participant observation involving 15 students who had adopted minimalist habits for at least six months. The findings show that the call to avoid isrāf (excess) is understood by students as a principle that shapes their choices in spending, organizing priorities, and managing time. Minimalism, in their view, reflects Islamic values such as moderation (wasatiyyah), contentment (qanā‘ah), and gratitude. It also supports clarity of mind, self-restraint, and a more focused approach to both academic and spiritual life. Several students described how this practice helped them respond to social pressures and consumerist habits within their peer and family environments. Rather than being seen as a trend or ideal, minimalism became part of how they carried their faith into daily routines. Surah Al-A‘raf verse 31, as they lived it, offered practical guidance in navigating choices—grounded not in theory, but in the rhythm of ordinary life.